CNN Based No‐Reference HDR Image Quality Assessment. Issue 2 (1st March 2021) - Kefeng, Fan; Jiyun, Liang; Fei, Li; Puye, Qiu
Abstract : Motivated by the problems of non‐universality and over‐reliance on the original reference image in High dynamic range (HDR) Image quality assessment (IQA), a convolutional neural network‐based algorithm for no‐reference HDR image quality assessment is proposed. The Salience detection by self‐resemblance (SDSR) algorithm which extracts the salient regions of the HDR image, is used to simulate the human visual attention mechanism. Then a visual quality perception network for training quality prediction models is designed according to the visual characteristics of luminance and contrast sensitivity. And this network consists of an Error estimation network (Error‐net), a Perceptual resistance network (PR‐net) and a mixing function. The experimental results indicate that the method proposed has high consistency with subjective perception, and the value of assessment metrics Spearman rank‐order correlation coefficient (SROCC), Pearson product‐moment correlation coefficient (PLCC) and Root mean square error (RMSE) correspondingly reaches 0.941, 0.910 and 8.176 as well. It is comparable with classic full‐reference HDR IQA methods.